Nausea and vomiting induced by pharmacotherapy: have all issues of maintenance therapy been resolved? - M. M. Konstantinova; R. M. Paltuev (ABV-press, 2023)
Many patients with various localizations of malignant neoplasms require therapy aimed at preventing or reducing the manifestations of nausea and vomiting induced by anticancer pharmacotherapy. New drugs to prevent the development of complications of chemotherapy are critical to improve the quality of life of patients and their adherence to therapy. Palonosetron, a new generation 5-HT3 receptor antagonist, has a long half-life (up to 40 hours) and a 30-fold higher affinity for 5-HT3 receptors compared to previous generations of 5-HT3 receptor antagonists. Clinical studies have shown the ability of palonosetron in combination with dexamethasone and, if indicated, neurokinin antagonists to effectively prevent the development of nausea and vomiting during single- and multi-day cycles of chemotherapy for both solid tumors and hematological diseases, including high-dose chemotherapy, in preparation for transplantation of auto- and allogeneic stem cells. The innovative oral drug Akynzeo is currently available for use in clinical practice, which includes 2 highly selective NK1 and 5-HT3 receptor antagonists in fixed doses. The drug prevents induced nausea and vomiting during moderate and highly emetogenic chemotherapy in more than 90 % of cases, both in the acute and delayed phases.